2013
DOI: 10.1111/odi.12118
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR‐31 and miR‐375 expression is associated with clinical outcomes in oral carcinoma

Abstract: This study has identified 19 miRNAs significantly associated with OSCC, and expressions of miR-31 and miR-375 were significantly related with clinico-pathological parameters suggesting they could be important in driving oral tumourigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 32 publications
1
49
2
2
Order By: Relevance
“…These results indicated that reduced expression levels of miR-375 may induce more aggressive tumor behavior during oral cancer progression. These results are similar to those reported by Siow et al (18), who demonstrated that low miR-375 expression levels were significantly associated with late-stage disease, larger tumor size and a non-cohesive pattern of invasion in OSCC.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicated that reduced expression levels of miR-375 may induce more aggressive tumor behavior during oral cancer progression. These results are similar to those reported by Siow et al (18), who demonstrated that low miR-375 expression levels were significantly associated with late-stage disease, larger tumor size and a non-cohesive pattern of invasion in OSCC.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed that miR-31 was emerging as an important regulator in carcinoma [15][16][17][18]. In the present study, we report that miR-31, a differentially expressed miRNA during fibrogenesis, significantly promotes HSC activation and migration.…”
Section: Introductionmentioning
confidence: 56%
“…Deregulated miR-375 expression has been indicated in various cancer types including oral carcinoma [17], breast cancer [18], esophageal adenocarcinoma, lung cancer [19], glioma [20], gastric cancer [21], and hepatocellular carcinoma [22]. More recently, elevated miR-375 expression was found in gastric cancer, and miR-375 can desensitize cells to ionizing radiation and etoposide by targeting p53 [23].…”
Section: Discussionmentioning
confidence: 97%